High Level Controller-Based Energy Management for a Smart Building Integrated Microgrid With Electric Vehicle - Dagdougui, Younes; Ouammi, Ahmed; Benchrifa, Rachid (Frontiers in Energy Research, 2020)
This paper presents an effective approach for the modelling and optimization of a smart building integrated microgrid (BIM). The main objective is the development of a smart building energy management system (BEMS) which is in charge of optimally controlling the operation of a building-integrated-microgrid. More specifically, we consider a BIM consisting of a roof-top solar photovoltaic, wind turbine, energy storage unit, electric vehicle, micro-CHP, metering infrastructure and loads. The BIM loads are associated to satisfy the electric needs of occupants as well as considering the operating flexibility of thermal load that includes building heating and hot water demand. The emphasis is given to the optimal performance of the BIM, where the objective is to ensure the power balance between production and loads in the microgrid (electric and thermal). A centralized algorithm is implemented for the power management of all components as well as power exchanges with the electrical grid. The developed algorithm is tested through a case study, where the effects of both loads and renewable resources variabilities on the operation of the BIM are analyzed via numerical simulations.